2016
DOI: 10.1111/jzs.12127
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the taxonomic status ofOsmoderma cristinae(Coleoptera: Scarabaeidae), endemic to Sicily, by genetic, morphological and pheromonal analyses

Abstract: Resolving complexes of closely related and cryptic insect species can be challenging, especially when dealing with rare and protected taxa that are difficult to collect for genetic and morphological analyses. Until recently, populations of the genus Osmoderma (Scarabaeidae), widespread in Europe, were treated as a single species O. eremita (Scopoli, 1763) in spite of observed geographic variation in morphology. A previous survey using sequence data from the mtDNA cytochrome C oxidase I gene (COI) revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…An integrated approach to the Italian populations, based on morphological and molecular analyses (Zauli et al 2016a), suggested that both the genetic distance (COI and AFLP markers) and morphological divergence (particularly the shape of male genitalia) support the validation of species rank for O. cristinae, despite the close relationship between this Sicilian endemic taxon and the widespread O. eremita. Additional poorly investigated taxa occur from the Balkan peninsula to the Caucasus mountains (apart from O. lassallei and O. barnabita): at least one undescribed species or semispecies, related to O. lassallei, in southern Greece (P. Audisio, P. Petrakis and G.M.…”
Section: Systematics and Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…An integrated approach to the Italian populations, based on morphological and molecular analyses (Zauli et al 2016a), suggested that both the genetic distance (COI and AFLP markers) and morphological divergence (particularly the shape of male genitalia) support the validation of species rank for O. cristinae, despite the close relationship between this Sicilian endemic taxon and the widespread O. eremita. Additional poorly investigated taxa occur from the Balkan peninsula to the Caucasus mountains (apart from O. lassallei and O. barnabita): at least one undescribed species or semispecies, related to O. lassallei, in southern Greece (P. Audisio, P. Petrakis and G.M.…”
Section: Systematics and Distributionmentioning
confidence: 99%
“…The problem arises when a locality is situated in the overlapping area between the ranges of two parapatric species, as in the case of O. eremita and O. barnabita in central Europe and the Balkans, where the possibility cannot be ruled out that they mated with each other. The less variable trait for separation of these two species is perhaps the shape of the parameres of the male genital organ (Krell 1997, Lüchte and Klausnitzer 1998, Sparacio 2000, Zauli et al 2016a according to the following key (see also Figure 3 The male genitalia also allow the separation of O. eremita and O. barnabita from O. cristinae, as the latter does not show a real upward extension on parameres but only a moderate swelling followed by a straight or very slightly convex slope continuing up to the base (Figure 4). However, genitalia shape cannot be used for monitoring populations because it requires dead specimens.…”
Section: Morphology and Comparison With Similar Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques confirmed this range of dispersal: 190m (Ranius and Hedin 2001) and 2,090m (Valainis et al 2015) with markrecapture studies, about 500m calculated with DNA markers (Oleksa et al 2013) and a maximum single flight distance of 1,454m and a maximum cumulative flight distance of 2,361m obtained with a flight mill (Dubois et al 2010). Dispersal is probably guided by the (R)-(+)-γ-decalactone, a pheromone emitted by males to attract females and sometimes also males in various other species of Osmoderma (Larsson et al 2003, Svensson et al 2009, Zauli et al 2016.…”
Section: Species Studiedmentioning
confidence: 99%
“…Sparacio, 2000, O. cristinae Sparacio, 1994and O. lassallei Baraud & Tauzin, 1991, respectively endemic to the Italian peninsula, Sicily and Greece and European Turkey (Sparacio 2000, Ranius et al 2005, Audisio et al 2007, Landvik et al 2013, Zauli et al 2016. Osmoderma species live in the cavities of large and old broad-leaved trees and, very likely, they all have the same biological requirements.…”
Section: Ethics Statementmentioning
confidence: 99%